The Impacts of Problem-Based Learning on English Vocabulary Mastery for Elementary Students - Hasnita; Iskandar; Nur Aeni (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2024)
In a globalized world, mastering English vocabulary is crucial for elementary students. This research investigates the effectiveness of Problem- In a globalized world, mastering English vocabulary is crucial for elementary students. This research investigates the effectiveness of Problem-Based Learning (PBL) in enhancing vocabulary acquisition compared to traditional methods. A quasi-experimental design was designed, and the study involved 20 students for the total sampling in the experimental group (receiving PBL instruction) and the control group (taught through traditional methods). Vocabulary proficiency was assessed through pre-tests and post-tests, and data were collected using paired t-tests to investigate within-group changes and independent t-tests to explore differences between groups. The Kolmogorov-Smirnov test confirmed normal distribution, while Levene's test indicated homogeneity. Results highlighted a significant boost in the experimental group, with a post-test mean score of 86.75 compared to the control group's 78.25. The paired t-test for the experimental group yielded a t-statistic of -12.862 (p = 0.000), exceeding the critical t-value of ±2.093, confirming PBL's effectiveness. The N-gain percentage was 59.09% for the experimental group and 35.83% for the control group, indicating a notable enhancement in vocabulary mastery through PBL. The study concludes that PBL significantly outperforms traditional methods in improving vocabulary skills. Recommendations include incorporating PBL into curricula to enhance vocabulary learning and conducting further research to explore its long-term effects and broader applicability. Based Learning (PBL) in enhancing vocabulary acquisition compared to traditional methods. Using a quasi-experimental design with total sampling, the study involved 20 students in both the experimental group (receiving PBL instruction) and the control group (taught through traditional methods). Vocabulary proficiency was assessed through pre-tests and post-tests, and data were conducted paired t-tests to investigate within-group changes, and independent t-tests to explore differences between groups.The Kolmogorov-Smirnov test confirmed normal distribution, while Levene's test indicated homogeneity. Results highlighted a significant boost in the experimental group.with a post-test mean score of 86.75 compared to the control group's 78.25. The paired t-test for the experimental group yielded a t-statistic of -12.862 (p = 0.000), exceeding the critical t-value of ±2.093, confirming PBL’s effectiveness. The N-gain percentage was 59.09% for the experimental group and 35.83% for the control group, indicating a notable enhancement in vocabulary mastery through PBL. The study concludes that PBL significantly outperforms traditional methods in improving vocabulary skills. Recommendations include incorporating PBL into curricula to enhance vocabulary learning and conducting further research to explore its long-term effects and broader applicability.